2013
DOI: 10.2147/vhrm.s49136
|View full text |Cite
|
Sign up to set email alerts
|

Serum calcium levels are not associated with coronary heart disease

Abstract: BackgroundNumerous studies have reported that low calcium intake is related to a higher prevalence of cardiovascular disease. However, the relationship between serum calcium and coronary heart disease is unclear. The purpose of this study was to compare serum calcium levels in patients with coronary heart disease and those in healthy individuals.MethodsThis retrospective, case-control study conducted in the People’s Republic of China comprised 380 cases and 379 controls. Serum calcium levels, blood lipids, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(20 reference statements)
0
2
1
Order By: Relevance
“…Additionally, they found a positive association between serum calcium and cardiovascular disease (10). In addition, Jin et al showed that serum calcium had no influence on coronary heart disease in the general population (15). Narang did not also find an association between serum calcium level and the angiographic severity in 376 stable patients with CAD (14), which was not in line with the results of the present study.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Additionally, they found a positive association between serum calcium and cardiovascular disease (10). In addition, Jin et al showed that serum calcium had no influence on coronary heart disease in the general population (15). Narang did not also find an association between serum calcium level and the angiographic severity in 376 stable patients with CAD (14), which was not in line with the results of the present study.…”
Section: Discussioncontrasting
confidence: 89%
“…On the other hand, calcium supplements with or without vitamin D showed no decrease; however, they modestly increased cardiovascular events, especially myocardial infarction (12,13). In addition, some studies revealed no correlation between serum calcium and cardiovascular event (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Data obtained by other researchers also indicates that in arterial hypertension the concentration of total calcium in the blood plasma remains constant [11][12][13][14][15]. A correlation between hypertension and serum calcium has been studied in different ethnicities and races [9,[16][17][18][19]. At the same time, a study of calcium metabolism in the body of patients with arterial hypertension revealed changes already in the early stages of the disease.…”
Section: Discussionmentioning
confidence: 92%